A Conceptual Framework on the Audit Quality in the Government Internal Audit in Indonesia - Aswar, Khoirul; Ermawati; Wiguna, Meilda; Hariyani, Eka (Information Management and Business Review, 2020)
This study begins with the problem of auditor performance on the Big Four Public Accounting Firm and requires an improvement in audit quality due to a decreased audit quality assessment on the Big Four Public Accounting Firm. Problem related to audit quality is also experienced by government internal auditors. This is due to several factors such as the minimum standards set by the Financial and Development Supervisory Agency (FDSA) that have not been met by government internal auditors, auditor staff with accounting education backgrounds are still very few, auditors have not applied the Government Internal Oversight Apparatus (GIOE) code of ethics and so forth. The aims of this study to determine the extent of the audit quality produced by the government’s internal auditors at the FDSA of Java island Representatives. Through the theory of behaviorism, this study has four objectives is to find out the implementation of professional accounting ethics, auditor competence, integrity, professional commitment on audit quality. Therefore, this study contributes to FDSA of Java Provinces to carry out the functions and duties of government internal auditor based on the GIOE codes and ethics and standards.